Diseño del proceso de producción de una bebida energizante a partir de la pulpa y semillas de Copoazú (Theobroma Grandiflorum) (2022)
This project arises as an innovative idea for the energy drinks market, due to the high demand for this type of product in different sectors of the population as an energy supplement to fulfill the different day-to-day activities. The proposal developed is a natural and innovative alternative in this field, given that the design of the energy drink production process stems from the use of the fruit of the Theobroma grandiflorum plant, thus generating added value to the product in terms of flavor and composition. In this way, the use of cupuassu as a raw material provides a content of proteins, minerals, vitamins and antioxidants, which give the drink nutritional value and imply benefits in terms of health.